2012
DOI: 10.1097/jan.0b013e31826f4bd6
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Stress, Coping, and Adaptation in Nurses in a Recovery and Monitoring Program

Abstract: Addiction rates in nurses are higher than in the general population. The relationship between stress, coping, and adaptation in nurses (N = 82) enrolled in a recovery and monitoring program in the state of New Jersey was examined. Social support, a variable tested as a mediator of this relationship, was also examined. Participants completed the Perceived Stress Scale, Multidimensional Scale of Perceived Social Support, and Psychological General Well-Being Index. Negative relationships were found between stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Initial analyses showed that gender differences emerged in the social support coping dimension: in particular, women were more likely to adopt social support as a coping strategy than men, in line with data from previous studies 23 . As discussed in the Introduction, social support seeking has been generally found to be a dysfunctional coping strategy in most of the studies which used the COPE‐NVI 22–24,26 . However, such gender‐based difference was not detected in subsequent analyses based on generalized linear models.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Initial analyses showed that gender differences emerged in the social support coping dimension: in particular, women were more likely to adopt social support as a coping strategy than men, in line with data from previous studies 23 . As discussed in the Introduction, social support seeking has been generally found to be a dysfunctional coping strategy in most of the studies which used the COPE‐NVI 22–24,26 . However, such gender‐based difference was not detected in subsequent analyses based on generalized linear models.…”
Section: Discussionsupporting
confidence: 65%
“…23 As discussed in the Introduction, social support seeking has been generally found to be a dysfunctional coping strategy in most of the studies which used the COPE-NVI. [22][23][24]26 However, such gender-based difference was not detected in subsequent analyses based on generalized linear models. In addition, women were less likely to use a coping style based on positive attitudes than men, in contrast with previous data.…”
Section: Socio-demographic and Work-related Moderators Of Coping Stra...mentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence demonstrates that peer support is an important structural factor that mitigates the effects of stress, improves the general well‐being of nurses recovering from PSU, and contributes to their positive treatment outcomes (Bowen, Taylor, Marcus‐Aiyeku, & Krause‐Parello, ; Darbro, ; Monroe et al., ). The literature also supports the effectiveness of structural interventions targeting peer support in positively shifting this structural influence.…”
Section: Culture Of the Nursing Professionmentioning
confidence: 99%